Inside Back Cover: An All‐Halogen Bonding Rotaxane for Selective Sensing of Halides in Aqueous Media (Angew. Chem. Int. Ed. 43/2014). Issue 43 (21st August 2014) - Mullaney, Benjamin R.; Thompson, Amber L.; Beer, Paul D.
<x xml:space="preserve">Abstract</x> Combining halogen bonding …︁ with an optical probe in an interlocked host design leads to a potent anion sensory system. As P. D. Beer et al. show in their Communication on page 11458 ff, an all‐halogen‐bonding rotaxane host with a photoactive rhenium(I) bipyridyl center in the macrocyclic component can optically sense halide anions by luminescence, with a high binding affinity and selectivity for iodide ions. Image: Dr. Karl Harrison.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>